LEVERAGING CUSTOMER DATA IN HYBRID OFFERING COMMERCIALIZATION : A Case Study from On-Road Load Handling - Siitonen, Olli (My University, 2021)
In recent years manufacturing companies have been increasingly transitioning towards more service-oriented business models with the hopes of gaining sustainable competitive advantage, increased profitability and increased customer loyalty. In connection with this transformation these industrial firms have made considerable investments into digitally connecting their manufactured equipment and are starting to amass vast amounts of operations data from this sensor equipped installed base. The research literature in this area has recognized that the customer data is a source of value, but its exploitation in pursuit of higher value creation has not been addressed. This study looks at reaping returns from these connected equipment investments by utilizing the collected data in hybrid offering commercialization process. This aim of the study was addressed through the three research questions: (1) What is required from manufacturing companies to move towards leveraging data from connected equipment? (2) How can manufacturing companies use the data in managing hybrid offering commercialization? (3) What are the key challenges and enablers in data driven commercialization process? This study was conducted as a single case study into a manufacturing company that had embarked into the connected equipment journey some 5 years ago. The study included a research literature review where relevant literary around hybrid offerings, new service development and connectivity were introduced as a basis for theoretical understanding. The data for empirical part of the study was collected through semi structured theme interviews with 8 case company representatives working with the connected equipment topics. The findings of this study contribute mainly to the field of data driven commercialization and digital servitization in industrial load handling setting. The findings identify the reasons behind connectivity investments, how it’s and the role of data has evolved during the 5-year journey to where it’s now key strategical pillar. The findings identify context specific ways how in industrial setting data can contribute to service development and customer intimacy. Constraining and enabling factors of data exploitation are identified to do with system legacy, market maturity, channel conflicts and intracompany factors. Lastly managerial implications are discussed, and future complementary research avenues are identified.
Keywords: Digital Servitization, Servitization, Hybrid Offerings, Data-driven commercialization